Piping manual for stainless steel pipes for buildings. (Japan Stainless Steel Association ; Nickel Institute, 2012)
In the building equipment sector, stainless steel pipe, which offers high corrosion resistance and solid strength, is used for air-conditioning piping systems for fluids including steam, chilled and hot water and cooling water, as well as for sanitary piping systems, such as water supply and hot-water supply. Since 2006, stainless steel pipe has also been used in piping systems for firefighting equipment. This 3rd revised edition of the technical manual includes all recent developments in corrosion resistance stainless steel pipes for building equipments.